2005
DOI: 10.1167/iovs.04-1304
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin and Turmeric Delay Streptozotocin-Induced Diabetic Cataract in Rats

Abstract: The results indicate that turmeric and curcumin are effective against the development of diabetic cataract in rats. Further, these results imply that ingredients in the study's dietary sources, such as turmeric, may be explored for anticataractogenic agents that prevent or delay the development of cataract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
238
1
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(266 citation statements)
references
References 35 publications
17
238
1
6
Order By: Relevance
“…The onset and progression of the cataract during experiment was monitored using a slit lamp biomicroscope (Kowa Portable, Japan) as described by us previously (21). Initiation, progression, and maturation of lenticular opacity were graded as described previously.…”
Section: Slit Lamp Examination and Cataract Classificationmentioning
confidence: 99%
“…The onset and progression of the cataract during experiment was monitored using a slit lamp biomicroscope (Kowa Portable, Japan) as described by us previously (21). Initiation, progression, and maturation of lenticular opacity were graded as described previously.…”
Section: Slit Lamp Examination and Cataract Classificationmentioning
confidence: 99%
“…Identification & Authentication of the rhizomes of curcuma longa and amla was done in Ayurvedic college of Bharati Vidyapeeth. Preparation was done as per the ayurvedic literature and standards compared with Ayurvedic pharmacopoeia of India [19]. All the animals were treated with the test drug and standard drug according to groups.…”
Section: Discussionmentioning
confidence: 99%
“…The fruit extract has many pharmacological activities for the treatment of a number of diseases and is a constituent of many hepatoprotective formulations [9]. Several recent reports revealed that fruit extract of Emblica officinalis protect against radiation [10], antiatherosclerosis [11], possess antidiabetic activity [12,13], inhibits aging process [14], gastroprotective [15], cytoprotective and immunomodulatory [16]. Despite its extensive medicinal use no information is available related to its use on alcoholinduced hepatotoxicity.…”
Section: Introductionmentioning
confidence: 99%